Intrauterine autologous platelet-rich plasma treatment in women with at least two implantation failures: A retrospective cohort study - Neda Fattahi Meybodi; Maryam Eftekhar; Behnaz Gandom (International Journal of Reproductive BioMedicine, 2024)
Abstract Background: Finding the most effective way to improve implantation rate in women who are receiving assisted reproductive technology treatment is still a challenge. Objective: This study aimed to assess the pregnancy outcomes of intrauterine platelet-rich plasma (PRP) therapy in women with a history of at least 2 implantation failures. Materials and Methods: In this retrospective cohort study, data of 852 women who were candidates for frozen-thawed embryo transfer was extracted from their medical records from April 2017 to September 2021 at Yazd Reproductive Sciences Institute, Yazd, Iran. Of these, 432 received intrauterine PRP treatment 48 hr before transfer (PRP group), and the results of the pregnancy outcomes compared with 420 of the control group who did not receive the treatment before transfer. Results: Pregnancy outcomes, including chemical, clinical, ongoing pregnancy, and live birth rate were statistically significant in the PRP group (p < 0.001). However, when categorized according to the implantation history, this significant improvement in all 4 was only seen in women with at least 2 prior implantation failures. In women with a history of only one implantation failure, PRP therapy significantly improved the ongoing pregnancy and live birth rate (19.5%, p = 0.04). Also, in women who received donor eggs and had repeated implantation failure, PRP improved pregnancy outcomes clinically but not statistically (p = 0.15). Conclusion: PRP seems to be effective in improving the pregnancy rate in women with a history of 2 or more implantation failures and also shows an increase in the live birth rate in women with only one implantation failure.